ANALYSIS OF FACTORS AFFECTING AUDITOR’S JUDGEMENTS: STUDY OF PUBLIC ACCOUNTING FIRM AUDITORS IN YOGYAKARTA - Bima Cinintya Pratama; Maulida Nurul Innayah (InFestasi, 2019)
Audit judgment is necessary because the audit cannot be conducted on all of the evidence. These evidence is used to express an opinion on the audited financial statements, so it can be said that the audit judgment also determining the outcome of the audit. This study aims to identify and analyze the factors that affect the auditor’s judgment in doing audit. This research was explorative research. The research methodology used in this research was factor analysis method. Technique used in collecting the data was questionnaire technique. The questionnaires were delivered to 72 auditors in public accounting firms in Yogyakarta. Fifty-six questionnaires (78%) were returned complete and could be processed. The results of the data analysis show that the auditor’s judgments in doing audit are influenced by factors of audit tenure, risk, professionalism, and attitude. Audit tenure becomes the dominant factor because it has the largest eigenvalues of 6.240. The implications of this study is that public accounting firms are expected to be aware to the audit tenure so close relationship will not exist that would affect the independence and objectivity of the auditor.